Chinese medicine for residual symptoms of COVID-19 recovered patients (long COVID)—A double-blind, randomized, and placebo-controlled clinical trial protocol - Sum, Chi Him; Ching, Jessica Yuet Ling; Song, Tianhe; Cheong, Pui Kuan; Lo, Cho Wing; Lai, Mei Kwan; Chia, Chon Pin; Chan, Kam Leung; Mak, Wing Yan; Leung, Ka Chun; Leung, Sin Bond; Zhang, Hongwei; et al. (Frontiers in Medicine, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) is the current global pandemic of which residual symptoms exhibited by post-acute, rehabilitating patients include fatigue, dyspnoea and insomnia. Chinese medicine (CM) has been widely used in China to treat different stages of COVID-19. While there are a significant number of clinical studies suggesting its efficacy and safety in its use during acute stage, there are very few randomized controlled trials focusing on the rehabilitation stage. Liujunzhi Decoction and Shashen Maidong Decoction are frequently recommended by official clinical guidelines in China to treat COVID-19 patients in rehabilitation stage. This double-blind, randomized, placebo controlled study aims to evaluate the efficacy and safety of the combination of the two formulae (named “COVID-19 Rehab Formula (CRF)”) in treating COVID-19 residual symptoms (long COVID). Methods: Eligible subjects will be randomly divided into treatment group and control group in 1:1 ratio. Treatment group will receive CRF along with certain pre-defined CM according to symptoms for 8 weeks, while control group will receive equivalent packs of placebo for 8 weeks. Data in terms of Fatigue Severity Score (FSS), self-reported COVID-19 long term symptom assessment, the modified British Medical Research Council (mMRC) Dyspnoea Scale, EuroQol Five-Dimension Five-Level (EQ-5D-5L) Questionnaire, pulmonary function test and adverse events will be collected and analysed by SPSS 24. Blood test on liver and renal functions will also be conducted as safety measures. Conclusion: This study will evaluate the efficacy and safety of CRF in the treatment COVID-19 residual symptoms in a scientifically rigorous design.